Stories of true crime in Tudor and Stuart England
1 online resource
Keywords: "Now in its second edition, Stories of True Crime in Tudor and Stuart England has been updated to include more texts about witchcraft, murder, and sexual deviance and discussions about the historical climate within which crimes occurred, voice and print culture, and types of crime and criminals. With five new chapters and an updated introduction and bibliography, the second edition of Stories of True Crime in Tudor and Stuart England is an essential resource for all students of crime and punishment in early modern England"--